Effect Of Mechanisation On Occupational Health And Safety Performance In The Nigerian Construction Industry - Idoro, Godwin Iroroakpo (Penerbit Universiti Sains Malaysia, 2011)
The need to improve productivity, quality standards, effciency and performance in construction projects has brought about increased use of Plant and Equipment (P&E). This study evaluates the level of mechanisation and its relationship to the Occupational Health and Safety (OHS) performance of the Nigerian construction industry. The purpose of the study is to ascertain the inﬂuence of mechanisation on OHS performance and raise the commitment of contractors to effective OHS management. To achieve this, a questionnaire survey involving 45 projects was conducted. Data were collected with the aid of structured questionnaires and analysed by percentages, means, t-tests and Spearman’s correlation tests. The results indicated that increased mechanisation leads to increased rates of accident and injury and that the level of mechanisation varies from one operation to another. The study concludes that mechanisation can worsen the OHS performance of the industry when it is not effectively managed. The fndings suggest that stakeholders should put effective measures in place aimed at controlling OHS performance before using new or additional P&E. They also suggest that stakeholders of specifc contractors should provide more attention when setting up an OHS management plan, particularly a hazard management plan regarding the on-site use of P&E.